2014
DOI: 10.1093/nar/gku793
|View full text |Cite
|
Sign up to set email alerts
|

Ms1, a novel sRNA interacting with the RNA polymerase core in mycobacteria

Abstract: Small RNAs (sRNAs) are molecules essential for a number of regulatory processes in the bacterial cell. Here we characterize Ms1, a sRNA that is highly expressed in Mycobacterium smegmatis during stationary phase of growth. By glycerol gradient ultracentrifugation, RNA binding assay, and RNA co-immunoprecipitation, we show that Ms1 interacts with the RNA polymerase (RNAP) core that is free of the primary sigma factor (σA) or any other σ factor. This contrasts with the situation in most other species where it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(75 citation statements)
references
References 72 publications
(93 reference statements)
10
65
0
Order By: Relevance
“…controversial (23,56,59), we previously demonstrated its presence and function (15,20,44), and we confirmed its presence by real-time PCR in the present study in mouse liver tissue (data not shown). We acknowledge that several signaling pathways are likely to be involved in this phenomenon.…”
Section: Discussionsupporting
confidence: 87%
“…controversial (23,56,59), we previously demonstrated its presence and function (15,20,44), and we confirmed its presence by real-time PCR in the present study in mouse liver tissue (data not shown). We acknowledge that several signaling pathways are likely to be involved in this phenomenon.…”
Section: Discussionsupporting
confidence: 87%
“…Differential proteomics suggests roles for 6S-2 in metabolism, an observation probably also applying to other bacterial species (Hoch et al, 2015;Steuten et al, 2014). A related case may be Ms1, a mycobacterial sRNA that interacts with core RNApol (Hnilicova et al, 2015).…”
Section: Protein Sequestratorsmentioning
confidence: 98%
“…At least one RNA identified based on its structural similarity to 6S RNA (Ms1 RNA in Mycobacterium smegmatis ) does not bind to the holoenzyme form of RNA polymerase, although it does interact with core RNA polymerase (60, 61). This example serves as a cautionary tale in relying too heavily on secondary structure as the predictor of 6S RNA candidates, but also raises the intriguing possibility that there are additional classes of sRNAs that function through interaction with RNA polymerase using different mechanisms.…”
Section: S Rnas Are Widespread Throughout the Bacterial Kingdommentioning
confidence: 99%